Inhibitor of DNA binding proteins revealed as orchestrators of steady state, stress and malignant hematopoiesis - Singh, Shweta; Sarkar, Tanmoy; Jakubison, Brad; Gadomski, Stephen; Spradlin, Andrew; Gudmundsson, Kristbjorn O.; Keller, Jonathan R. (Frontiers in Immunology, 2022)
Adult mammalian hematopoiesis is a dynamic cellular process that provides a continuous supply of myeloid, lymphoid, erythroid/megakaryocyte cells for host survival. This process is sustained by regulating hematopoietic stem cells (HSCs) quiescence, proliferation and activation under homeostasis and stress, and regulating the proliferation and differentiation of downstream multipotent progenitor (MPP) and more committed progenitor cells. Inhibitor of DNA binding (ID) proteins are small helix-loop-helix (HLH) proteins that lack a basic (b) DNA binding domain present in other family members, and function as dominant-negative regulators of other bHLH proteins (E proteins) by inhibiting their transcriptional activity. ID proteins are required for normal T cell, B cell, NK and innate lymphoid cells, dendritic cell, and myeloid cell differentiation and development. However, recent evidence suggests that ID proteins are important regulators of normal and leukemic hematopoietic stem and progenitor cells (HSPCs). This chapter will review our current understanding of the function of ID proteins in HSPC development and highlight future areas of scientific investigation.